Daptomycin > 6 mg/kg/day as salvage therapy in patients with complex bone and joint infection: cohort study in a regional reference center. Issue 1 (December 2016) - Roux, Sandrine; Valour, Florent; Karsenty, Judith; Gagnieu, Marie-Claude; Perpoint, Thomas; Lustig, Sébastien; Ader, Florence; Martha, Benoit; Laurent, Frédéric; Chidiac, Christian; Ferry, Tristan
Abstract Background Even if daptomycin does not have approval for the treatment of bone and joint infections (BJI), the Infectious Diseases Society of America guidelines propose this antibiotic as alternative therapy for prosthetic joint infection. The recommended dose is 6 mg/kg/d, whereas recent data support the use of higher doses in these patients. Methods We performed a cohort study including consecutive patients that have received daptomycin >6 mg/kg/d for complex BJI between 2011 and 2013 in a French regional reference center. Factors associated with treatment failure were determined on univariate Cox analysis and Kaplan-Meier curves. Results Forty-three patients (age, 61 ± 17 years) received a mean dose of 8 ± 0.9 mg/kg/d daptomycin, for a mean 81 ± 59 days (range, 6–303 days). Most had chronic (n  = 37, 86 %) implant-associated (n  = 37, 86 %) BJI caused by coagulase-negative staphylococci (n  = 32, 74 %). A severe adverse event (SAE) occurred in 6 patients (14 %), including 2 cases of eosinophilic pneumonia, concomitant with daptomycin Cmin >24 mg/L. Outcome was favorable in 30 (77 %) of the 39 clinically assessable patients. Predictors for treatment failure were age, non-optimal surgery and daptomycin withdrawal for SAE. Conclusions Prolonged high-dose daptomycin therapy was effective in patients with complex BJI. However, optimal surgery remains the cornerstone of medico-surgical strategy; and a higher incidence of eosinophilic pneumonia than expected was recorded.